Competividade de fruticultura brasileira no mercado internacional - Cunha Filho, Miguel Henrique da (2005)
In the present study, we work with evolution of Brazilian fruit-growing competitivity in international market from 1990 to 2003, adopting as theoretical basis the international trade models and the competitivity concept. To this analysis we searched the primary exported products as well as the most important bound market. The used methodology was based on tabular and graphical analysis and on the participation indicators of commercial liquidation in the GDP sector calculation, relative position of the sector on world’s market, revealed comparative advantage, covering tax, concentration index and performance indicator. Were applied yet annual growing rates, calculated based on arithmetics average. The results pointed out a growth and a proeminent insertion of Brazilian fruit-growing in the international market, with relative competitivity gains. This sector, though, still presents a very concentrated structure so with respect to the product as with respect to the bound market of its exportations. In this way, it is necessary to solve some internal and external encumbrances in order to search options to increase exportations and consequently Brazilian fruit-growing competitivity.